ANALISIS SISA UMUR PAKAI PIPA PENYALUR FUEL B.35 DI PLTMG AMBON PEAKER 30 MW - Josua M. Leatemia; Nevada J.M Nanulaitta; Berthy Pelasula (Department of Mechanical Engineering, 2024)
Pipeline systems are one way to deliver fuel from refineries to distribution points before it reaches consumers. The system consists of a number of pipes that transport the fluid over a considerable distance. An underground pipeline system is the system used in this design analysis. The technical requirements for the construction and planting of underground pipe systems will have an impact on the pipeline pressure. In this study is how to determine the Remain life of the fuel B.35 pipeline at the PLTMG Ambon Peaker 30 MW. Conducting a thickness testing method with an ultrasonic thickness gauge measuring instrument. In this test, researchers will carry out a series of stages, starting from pipe preparation and characterization to understand the initial condition of the pipeline. Afterwards, testing is carried out using an ultrasonic thickness gauge that not only focuses on the thickness of the pipe, but also on the overall structural integrity.This study was conducted by measuring the thickness of the pipe to obtain preliminary data to measure the remaining service life of the B.35 fuel distribution pipe from the holding tank to the daily tank. Measurement using ultrasonic thickness gauge. The length of the inspected pipe is 78 m divided into 13 staff, with 624 measurement points divided into 48 points per staff. The lowest remaining pipe life value is 13,5 years and the highest is in the 10th staff pipe worth 20,1 years. Keywords: pipe thickness, corrosion rate and remaining pipe service life